Integrasi Ilmu Hukum Dan Teologisebagai Satu Kesatuan Etika Moralitas - Sambo, Ferdy (Publikasi Indonesia, 2025)
This study aims to determine and find the integration of legal science and theology as a single unit of moral ethics. This type of research is a qualitative post-positivist research. The research method used is a qualitative post-positivist research method with a descriptive approach. Data collection used is library books and literature, surveys, interviews that are appropriate as references. Research Subject Integration of Legal Science and Theology as a single unit of moral ethics. Research Object Integration of Legal Science and Theology as a single unit of moral ethics. The results of the study found that the Integration of Legal Science and Theology as a single unit of moral ethics can help increase moral awareness and form good behavior in various situations.